Performance Analysis of Propagation Models for WiMAX Network - Milud Moftah Mohamed Daw; Mohammed Awadh Ben-Mubarak (African Journal of Advanced Pure and Applied Sciences, 2023)
At present, became the joint action in worldwide about access Microwave (WiMAX) technology, also became more popular and receive growing acceptance as a wireless broadband access system (BWA). WiMAX can success at line-of-sight (LOS) and non-line-of-sight (NLOS) cases that working below 11GHz frequency. However, path loss calculation or estimation is so important criteria to improve the WiMAX network performance. There are many of pr6+opagation models (e.g., COST 231 HATA Model, Hata Mode which can estimate of path loss. This paper we will analysis and compare between three of propagation models (COST 231 HATA, ECC-33, HATA) in various receiver antenna heights (3m, 6m, 10m) in urban areas. Results show that the ECC-33 model is the best compare with HATA model and COST 231 HATA model.